Perancangan Sistem Lelang Online Berbasis Website - Salman Farisi; Arie Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Website-based online auction system is a system of making the auction process system of making and marketing auction products and payment processes through third parties as payment verifiers made with information system media. So the seller can market products with a broader scope and users can transact comfortably because there is a middleman, that is admin as a verifier. Can be found in the online auction system that is on Facebook is Facebook Required the container in accordance with the auction process that is marketed can not be accessed in all easy access and all information updates are still using a manual system that requires auctions and payment processes that are still done manually. the purpose of this research is to create an online auction system based on this site to make an official website so that users can be more specific and update the detailed information of the offer is automated and the payment process through the admin as a verifier. research methods conducted using prototyping development methods with UML system modeling.